Kontribusi Kuwait Dalam Mediasi Konflik Qatar Dengan Arab Saudi 2017-2019 - Dewi, Nabilah Ratna; Utama, Tri Cahya; Pattipelhy, Shary Charlotte Henriette (Journal of International Relations, 2021)
In 2017 there was a diplomatic crisis among members of The Gulf Cooperation Council (GCC), specifically between Saudi Arabia and its regional allies, namely the United Arab Emirates, Egypt, Bahrain, Yemen and Qatar. The crisis caused Saudi Arabia and several of its allies to blockade Qatar. This study aims to analyze the contribution of Kuwait as a mediator in the conflict between Qatar and Saudi Arabia. The data collection method used is a secondary method. This study uses qualitative data analysis techniques. Based on the results of the analysis, it is known that as a form of contribution in resolving the Arab-Qatar conflict, Kuwait made several efforts, namely: efforts through bilateral meetings with conflicting parties and efforts through the GCC Summit. Kuwait's mediation efforts met a bright spot at the 41st GCC Summit in 2021 which was held in Riyadh, Saudi Arabia. This summit resulted in a peace agreement between Saudi Arabia and Qatar. The causes of Kuwait's contribution to mediating the conflict between Qatar and Saudi Arabia can be divided into two factors, namely: internal and external. Internal factors consist of political and economic factors. The external factors are related to regional security.